High-efficiency spot size converter for photonic crystal fiber-to-waveguide using composite waveguide structures - Li, Haoyu; Li, Baoshuai; Zhuang, Xingang; Chen, Lingyun; Wu, Bin; Zhao, Luo; Zhu, Xingbang; Gao, Yesheng; Wu, Hengkui (Frontiers in Physics, 2024)
This paper presents the design of a high-efficiency spot size converter (SSC) for photonic crystal fiber (PCF) to silicon-based waveguides, utilizing composite optical waveguide structures. The SSC is composed of a series of waveguide cores, with one core progressively widening to enable all cores to collectively serve as a composite input port, while the broader core functions as the output port. Simulation results reveal that the proposed design efficiently facilitates mode and energy transfer between the waveguide and the PCF, achieving a coupling efficiency of up to 93.99% over a length of 66 μm. Additionally, the SSC exhibits polarization insensitivity, with the high circularity of the output beam enhancing vertical alignment tolerance, and maintaining excellent performance over a wide wavelength range. In sum, this SSC demonstrates excellent coupling efficiency and holds significant promise for applications in optical communication systems and optical integrated circuit systems.